B Vitamins and Cognitive Performance in Older Adults: Review. (11th March 2013) - Reay, J. L.; Smith, M. A.; Riby, L. M.
Abstract : A copious amount of scientific scrutiny has been dedicated to documenting typical and atypical human ageing, with a substantial body of work focusing upon the impact of lifestyle choices. One such lifestyle choice is that of diet and, in particular, micronutrient ingestion. Epidemiological studies have reported positive associations between B vitamin status and cognitive function, including negative associations between biological markers (i.e., homocysteine) of dysregulated one-carbon metabolism and cognitive function. This has led to a surge of randomised control trials (RCTs) investigations into B vitamin therapy. However, results have continuingly failed to show beneficial behavioural effects. Despite this, results reliably show treatment-related increases in B vitamin level and decreases in homocysteine level—both of which have been identified as risk factors for atypical ageing. In this paper we argue that it would be premature to conclude that B vitamin therapy has no potential and that more research is needed to systematically investigate the optimal dose, the therapeutic "window, " and individual differences in therapy responders and nonresponders. We start with a brief look at one-carbon metabolism and then consider the evidence from epidemiological studies and RCTs in relation to three specific B vitamins: folic acid (B9), pyridoxine (B6), and cobamides (B12).